センジョウ ビデオ サツエイ ニヨル ナンキョク エンガンイキ ノ カイヒョウ ジョウキョウ - 下田, 春人; シモダ, ハルト; 遠藤, 辰雄; エンドウ, タツオ; 村本, 健一郎; ムラモト, ケンイチロウ; 小野, 延雄; オノ, ノブオ; 滝沢, 隆俊; タキザワ, タカトシ; 牛尾, 収輝; ウシオ, シュウキ; et al. (1997)
P(論文) 第30,31,32次日本南極地域観測隊が「しらせ」艦上で撮影した氷況観測ビデオ映像を用いて, 海氷の密接度, 氷厚を定量化した。解析を行った区間は, 30,31次ではブライド湾進入時, ブライド湾～昭和基地の2区間, 32次ではプリンスオラフ海岸沖進入時, プリンスオラフ海岸沖～ブライド湾, ブライド湾～昭和基地の3区間についてである。その結果, 各年による「しらせ」航路上の海氷状況の違い, 緯度による氷厚の変化, 30次と32次のリュツォ・ホルム湾内氷厚の年較差を調べることができた。また, 同時に計測された短波放射計を用いてアルベドを求め, 得られた密接度と比較し比例関係が求められた。さらに, 海氷域接地気層の鉛直温度傾度を求め, 密接度と比較した。 During the 30th, 31st, and 32nd Japanese Antarctic Research Expeditions (JARE-30,JARE-31,and JARE-32), sea-ice conditions were recorded by video camera on board the SHIRASE. Then, the sea-ice images were used to estimate compactness and thickness quantitatively. Analyzed legs are those toward Breid Bay and from Breid Bay to Syowa Station during JARE-30 and JARE-31,and those toward the Prince Olav Coast, from the Prince Olav Coast to Breid Bay, and from Breid Bay to Syowa Station during JARE-32. The results show yearly variations of ice compactness and thickness, latitudinal variations of thickness, and differences in thickness histograms between JARE-30 and JARE-32 in Lutzow-Holm Bay. Albedo values were measured simultaneously by a shortwave radiometer. These values are proportional to those of ice compactness. Finally, we examined the relationship between ice compactness and vertical gradient of air temperature above sea ice. departmental bulletin paper